2018
DOI: 10.1039/c8ra04663h
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizer-loaded biomimetic platform for multimodal imaging-guided synergistic phototherapy

Abstract: Photodynamic therapy (PDT) has attracted much attention as a strategy for tumor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It is hence very interesting that PTT-PDT synergistic therapy can be, at least in principle, simply achieved by functionalizing MNP with PS. Also for this application surface control is important and Tian et al adopted PEG modification to improve tumor-targeting ability, circulation time and biocompatibility of MNP [ 221 ]. Their PDMN–Ce6 NP were formed by the successful surface loading of Ce6 to PDA NP via π-π stacking, which were afterwards PEGylated.…”
Section: Mnp Based Therapy and Theranosticsmentioning
confidence: 99%
“…It is hence very interesting that PTT-PDT synergistic therapy can be, at least in principle, simply achieved by functionalizing MNP with PS. Also for this application surface control is important and Tian et al adopted PEG modification to improve tumor-targeting ability, circulation time and biocompatibility of MNP [ 221 ]. Their PDMN–Ce6 NP were formed by the successful surface loading of Ce6 to PDA NP via π-π stacking, which were afterwards PEGylated.…”
Section: Mnp Based Therapy and Theranosticsmentioning
confidence: 99%
“…Synthetic melanin nanoparticles (SMNPs) are an important class of biobased synthesized nanomaterials that have been used as multimodal imaging agents, , photothermal agents, , drug-delivery systems for chemotherapy, and in the fabrication of stimuli-responsive films . In humans, melanins play a diverse role in biological functions such as coloration, chelation, photoprotection, thermoregulation, and quenching of free radicals .…”
Section: Introductionmentioning
confidence: 99%
“…PDMNs were prepared based on the reported approach. , The transmission electron microscope (TEM) images revealed that the PDMNs had a spherical shape with an average diameter of approximately 100 nm, and the small-molecule JQ1 loaded onto the PDMN via π–π stacking interactions did not significantly change its size and dispersion from the PDMN-JQ1 TEM (Figure a). As shown in Figure b, the representative absorption peaks of JQ1 were also found in the Fourier transform infrared spectroscopy (FT-IR) spectrum of PDMN-JQ1.…”
Section: Resultsmentioning
confidence: 99%